Preparation and characterisation of TiO2 thick films fabricated by anodic oxidation in sulphuric acid - H. Z., Abdullah; C. C., Sorrell (Universiti Malaysia Perlis, 2010)
International Conference on X-Rays and Related Techniques in Research and Industry (ICXRI 2010) jointly organized by Universiti Malaysia Perlis (UniMAP) and X-Ray Application Malaysia Society (XAPP), 9th - 10th June 2010 at Aseania Resort Langkawi, Malaysia.